Student satisfaction and types of interaction in distance education courses - Keeler, Leslie Cordie, author; Carlson, Laurie A., advisor; Quick, Don, advisor; Yohon, Teresa I., committee member; Zimmerman, Donald E., committee member (Colorado State University. Libraries, 2006)
Technology developments have enabled more collaboration and interaction of learners with instructors, other learners, and the content in distance education courses. A complex array of factors combine to make distance education course experiences varied for students in higher education. This study looked at what types of interaction are most important to student satisfaction in distance education courses. An instrument was developed to evaluate the types of interaction in relation to student satisfaction. The initial instrument items were outlined through a review of the literature and other instruments of instructional evaluation. The framework for the Student Satisfaction and Interaction Questionnaire (SSIQ) was given to a panel of experts, who conducted multiple item reviews and content validation using the Index of Item-Objective Congruence. The hypothesis for this study was that there would not be any one type of interaction that better predicts student satisfaction in a distance education course. The SSIQ was placed on the World Wide Web and graduate students in a distance Master of Business Administration program were sent e-mails announcing their selection to participate in the survey, along with a URL link to a letter of invitation. After collecting completed survey data from the participants, descriptive statistics such as item frequencies, means, and standard deviations were calculated. Themes from the comments were analyzed. Simultaneous multiple regression was conducted to determine the best linear combination of interaction types for predicting overall student satisfaction in distance education courses. The combination of variables (interaction types - learner-content, learner-instructor, learner-learner, and learner-multiple) significantly predicted overall student satisfaction in distance education courses. The findings suggest that learner-instructor interaction contributed the most to overall student satisfaction in distance education courses, with learner-content interaction also significant to the model. Seventy-two percent of the variance in overall student satisfaction in distance education courses was explained by learner-instructor and learner-content interactions. This is a larger than typical effect in terms of practical significance (n = 105). The outcomes were further validated through the qualitative research question where students were asked to rank-order the survey constructs (learner-content, learner-instructor, learner-learner, and learner-multiple interaction types). The research results showed that both learner-content and learner-instructor interaction were the most important types of interaction to the participants in a distance education course. Recommendations for practice and future research needs are discussed.
Keywords: higher education; adult education; continuing education; educational technology